1990
DOI: 10.1037/0012-1649.26.5.710
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and inhibitory control in normal development and childhood psychopathology.

Abstract: Two experiments investigated the development and pathology of inhibitory control in children. Inhibitory control was investigated with the stop-signal paradigm, which is based on a formal theory of inhibition and directly measures the mechanism of inhibition. The ability to inhibit developed little after Grade 2, but subjects with attention deficit disorder with hyperactivity (ADDH) showed deficient inhibitory control. Their deficient inhibitory control was attributable to the subgroup of ADDH subjects with pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
381
4
6

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 433 publications
(416 citation statements)
references
References 37 publications
25
381
4
6
Order By: Relevance
“…This is important, because one of the most robust effects of MPH is to reduce the variability of response times (Coons, Klorman, & Borgstedt, 1987;Peloquin & Klorman, 1986), which in turn might enhance the observed probability of inhibiting ongoing responses (Logan, 1994;, despite any concomitant adverse effects of the medication on the efficiency of the inhibitory processes. The theoretical assumptions and predictions of the model have been validated empirically in numerous studies of adults (e.g., De Jong et al, 1990;, Osman et al, 1990 and more recently have also been validated in children (Schachar & Logan, 1990;Schachar et al, in press). …”
Section: Methods For Assessing Cognitive Flexibilitymentioning
confidence: 97%
See 2 more Smart Citations
“…This is important, because one of the most robust effects of MPH is to reduce the variability of response times (Coons, Klorman, & Borgstedt, 1987;Peloquin & Klorman, 1986), which in turn might enhance the observed probability of inhibiting ongoing responses (Logan, 1994;, despite any concomitant adverse effects of the medication on the efficiency of the inhibitory processes. The theoretical assumptions and predictions of the model have been validated empirically in numerous studies of adults (e.g., De Jong et al, 1990;, Osman et al, 1990 and more recently have also been validated in children (Schachar & Logan, 1990;Schachar et al, in press). …”
Section: Methods For Assessing Cognitive Flexibilitymentioning
confidence: 97%
“…The "checked swing" phenomenon in baseball or cricket provides a useful analogy for this inhibitory action (De Jong, Coles, Logan, & Gratton, 1990;Osman, Kornblum, & Meyer, 1990). Of relevance here are the findings that children with ADHD exhibit deficits in response inhibition (Pliszka & Borcherding, 1994;Schachar & Logan, 1990;Schachar, Tannock, Marriott, & Logan, in press), so that any further impairment in this cognitive process as a result of stimulant treatment would be of great concern. We found that stimulants enhanced the response inhibition processes (Tannock et al, 1989a).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Perhaps the most fundamental deficit in ADHD is the lack of response inhibition [52] . In laboratory studies of tasks that measure inhibitory control, children with ADHD often perform more poorly than both normal controls and children with other psychiatric disorders [59,60] .…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most fundamental deficit in ADHD is the lack of response inhibition [52] . In laboratory studies of tasks that measure inhibitory control, children with ADHD often perform more poorly than both normal controls and children with other psychiatric disorders [59,60] .Schulz et al reported that response inhibition in adolescents diagnosed with ADHD is primarily mediated by fronto-striatal circuitry [61,62] . …”
mentioning
confidence: 99%